Managing Post-Disaster Needs Assessments (PDNA) - Jones, Brett (World Bank, Washington, DC, 2012)
This knowledge note provides an overview of the post-disaster assessment process, extracting lessons learned in the East Asia Pacific Region (EAP) and presenting best practices from recent assessments. The note explains the Post-Disaster Needs Assessment (PDNA) methodology, and outlines: (i) the assessment triggers, (ii) key steps in assessment planning, and (iii) dos and don'ts in assessment execution. More in-depth guidance is available in UNECLAC's 'Handbook for Estimating the Socioeconomic and Environmental Effects of Disasters' and 'TTL Guidance for Conducting Damage and Loss Assessments after Disasters' prepared by the Global Facility for Disaster Reduction and Recovery (GFDRR).